2012
DOI: 10.1002/pssc.201200317
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of InGaN/GaN nanocolumns in yellow‐to‐red region

Abstract: The optical properties of InGaN/GaN multiple‐quantum‐well (MQW) nanocolumns whose emission wavelength is in the yellow‐to‐red region (2.1 ∼ 2.3 eV) have been investigated using time‐resolved photoluminescence (PL) measurements. The analysis of the PL decay curves using a stretched exponential function shows that the radiative and nonradiative rates in the red region are almost the same as those in the yellow region. Long‐lived migrating carriers also contribute the strong PL intensity in the red region. (© 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With the use of tunnel junction, the resistive p -GaN contact layer can be replaced by an n -GaN contact, leading to significantly reduced device resistance, , voltage loss, and heating effect. , Tunnel junction also enables the stacking of multiple p – n junctions/LEDs, ,, providing the unique opportunity of repeated carrier usage. ,, As such, high power operation can be achieved at low injection current, leading to enhanced efficiency and reduced efficiency droop. , Various design schemes, including GaN/Al­(Ga)­N/GaN, , GaN/InGaN/GaN, ,, and GaN/GdN/GaN , tunnel junctions have been implemented in GaN-based LED structures. However, the tunneling probability has been severely limited by the difficulty in creating a highly doped p -region. ,, Recently, it has been demonstrated that dopant incorporation can be significantly enhanced in nanowire structures, due to the much reduced formation energy in the near-surface region. Moreover, compared to conventional GaN quantum well devices, GaN nanowire LEDs can exhibit significantly reduced dislocation densities and polarization fields. Nanowire LEDs with tunable, multicolor emission have been demonstrated, which can be epitaxially grown on extremely low cost, large area Si substrates. , In spite of these intensive studies, the incorporation of tunnel junction in nanowire LEDs has not been reported to our knowledge.…”
mentioning
confidence: 99%
“…With the use of tunnel junction, the resistive p -GaN contact layer can be replaced by an n -GaN contact, leading to significantly reduced device resistance, , voltage loss, and heating effect. , Tunnel junction also enables the stacking of multiple p – n junctions/LEDs, ,, providing the unique opportunity of repeated carrier usage. ,, As such, high power operation can be achieved at low injection current, leading to enhanced efficiency and reduced efficiency droop. , Various design schemes, including GaN/Al­(Ga)­N/GaN, , GaN/InGaN/GaN, ,, and GaN/GdN/GaN , tunnel junctions have been implemented in GaN-based LED structures. However, the tunneling probability has been severely limited by the difficulty in creating a highly doped p -region. ,, Recently, it has been demonstrated that dopant incorporation can be significantly enhanced in nanowire structures, due to the much reduced formation energy in the near-surface region. Moreover, compared to conventional GaN quantum well devices, GaN nanowire LEDs can exhibit significantly reduced dislocation densities and polarization fields. Nanowire LEDs with tunable, multicolor emission have been demonstrated, which can be epitaxially grown on extremely low cost, large area Si substrates. , In spite of these intensive studies, the incorporation of tunnel junction in nanowire LEDs has not been reported to our knowledge.…”
mentioning
confidence: 99%